2014
DOI: 10.1002/chem.201303747
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Ion‐Regulated Miniature DNA‐Binding Proteins Based on GCN4 and Non‐native Regulation Sites

Abstract: The design of artificial peptide dimers containing polypyridine switching domains, for which metal-ion coordination is shown to regulate DNA binding, is reported. Short peptides, based on the basic domain of the GCN4 transcription factor (GCN4bd), dimerised with either 2,2'-bipyridine (bipy(GCN4bd) 2 ) or 2,2':6',2''-terpyridine (terpy(GCN4bd) 2 ) linker units, undergo a conformational rearrangement on Cu II and Zn II coordination. Depending on the linker substitution pattern, this is proposed to alter the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…In this study, we exploited this feature to demonstrate the ability of HCM-bearing peptides to recognize and bind a biological target. Starting with the pioneering work by Kim, 54,61 several synthetic strategies have been developed for the dimerization of bZIP peptides, 55,62-64 including disulfide bonding, 54 metal coordination, 65-68 and crosslinking with metal-tunable 69 or photo-switchable linkers. 70-72 These studies have collectively shown the importance of the dimeric organization of the basic domains as well as their proper orientation for DNA binding and recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we exploited this feature to demonstrate the ability of HCM-bearing peptides to recognize and bind a biological target. Starting with the pioneering work by Kim, 54,61 several synthetic strategies have been developed for the dimerization of bZIP peptides, 55,62-64 including disulfide bonding, 54 metal coordination, 65-68 and crosslinking with metal-tunable 69 or photo-switchable linkers. 70-72 These studies have collectively shown the importance of the dimeric organization of the basic domains as well as their proper orientation for DNA binding and recognition.…”
Section: Discussionmentioning
confidence: 99%
“…(g) Mascareñas' cis/trans azobenzene photoswitch linker . (h) Peacock's metal switch linker . (i) Peacock's photocontrolled anthracene dimer …”
Section: Dna‐binding Peptidesmentioning
confidence: 99%
“…This linker should undergo a conformational change upon metal ion coordination, which in turn should affect the relative orientation of the basic regions and influence the DNA binding of the dimer. CD and UV/Vis spectroscopy demonstrated that coordination of this metal‐chelating GCN4 dimer to Cu II or Zn II ions promoted DNA binding (Figure h) …”
Section: Dna‐binding Peptidesmentioning
confidence: 99%
“…Among the triggering stimuli, metal coordination is one of the most challenging strategies due to the abundance of metal ions in cells that can occupy the coordination sites of the synthetic systems and hamper the envisaged DNA interaction process. In this regard, Peacok’s team reported two short peptides connected by a bipyridine or a terpyridine unit that undergo conformational changes upon Zn 2+ or Cu 2+ coordination, prompting their interaction with double-stranded DNA (ds-DNA) [ 9 ]. An interesting system described by Learte-Aymami et al is composed of a peptide moiety containing histidine units, which is unable to bind DNA because of the unstructured nature in solution, but Pd 2+ coordination to the nitrogen atoms of the histidines promotes its folding, adopting a helical conformation with a concomitant high ds-DNA binding [ 10 ].…”
Section: Introductionmentioning
confidence: 99%